The functional role of platelets in the regulation of angiogenesis. (15th May 2014) - Walsh, Tony G.; Metharom, Pat; Berndt, Michael C.
Abstract: Functionally, platelets are primarily recognized as key regulators of thrombosis and hemostasis. Upon vessel injury, the typically quiescent platelet interacts with subendothelial matrix to regulate platelet adhesion, activation and aggregation, with subsequent induction of the coagulation cascade forming a thrombus. Recently, however, newly described roles for platelets in the regulation of angiogenesis have emerged. Platelets possess an armory of pro- and anti-angiogenic proteins, which are actively sequestered and highly organized in α-granule populations. Platelet activation facilitates their release, eliciting potent angiogenic responses through mechanisms that appear to be tightly regulated. In conjunction, the release of platelet-derived phospholipids and microparticles has also earned merit as synergistic regulators of angiogenesis. Consequently, platelets have been functionally implicated in a range of angiogenesis-dependent processes, including physiological roles in wound healing, vascular development and blood/lymphatic vessel separation, whilst facilitating aberrant angiogenesis in a range of diseases including cancer, atherosclerosis and diabetic retinopathy. Whilst the underlying mechanisms are only starting to be elucidated, significant insights have been established, suggesting that platelets represent a promising therapeutic strategy in diseases requiring angiogenic modulation. Moreover, anti-platelet therapies targeting thrombotic complications also exert protective effects in disorders characterized by persistent angiogenesis.